2022
DOI: 10.3762/bjoc.18.168
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of imidazole N-oxide: a recent discovery in organic transformations

Abstract: Nowadays heterocyclic compounds are widely used in medicinal chemistry and industry to develop life-saving drugs and medicines. Imidazole is one of the pharmacologically important heterocyclic motifs found in widely used and well-known medicines and bioactive molecules. The applications of imidazole derivatives displaying various biological activities, motivated researchers for the development of more potent and significant drugs containing imidazole moieties. The formation of imidazole derivatives can be achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…7 In this regard, the use of imidazoles in the form of readily available N -oxides provides additional rich capabilities. 8 The introduction of the N -oxide function significantly changes the reactivity of the parent heterocycle. The main feature is the possibility of imidazole N -oxides acting as dipoles in [3 + 2]-cycloaddition reactions with electron-deficient olefins, acetylenes, and other dipolarophiles.…”
Section: Introductionmentioning
confidence: 99%
“…7 In this regard, the use of imidazoles in the form of readily available N -oxides provides additional rich capabilities. 8 The introduction of the N -oxide function significantly changes the reactivity of the parent heterocycle. The main feature is the possibility of imidazole N -oxides acting as dipoles in [3 + 2]-cycloaddition reactions with electron-deficient olefins, acetylenes, and other dipolarophiles.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of the C(sp 2 )–H amination of heterocyclic compounds via CDC techniques, a fair number of studies throughout 2010s were focused on the functionalization of heteroaromatic azine N-oxides . Meanwhile, nonaromatic azaheterocyclic systems, such as cyclic aldonitrones (and cyclic azomethines in general), have got far less attention, notwithstanding their significant practical potential . In 2021, our research group reported the first example of the direct C(sp 2 )–H amination of model cyclic aldonitrones, 2 H -imidazole 1-oxides, by action of NH-containing azoles (Scheme a) .…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, our research group reported the first example of the direct C­(sp 2 )–H amination of model cyclic aldonitrones, 2 H -imidazole 1-oxides, by action of NH-containing azoles (Scheme a) . Such nitrones have been a subject of our particular interest due to their remarkable benchtop stability combined with synthetic versatility within a C–H functionalization paradigm, allowing one to obtain rather complicated polyfunctional heterocyclic compounds in a step-efficient manner . In this work, we extend our study on C–H amination of imidazole oxides, passing from their reactions with NH-azoles toward those with more conventional cyclic amines (Scheme b).…”
Section: Introductionmentioning
confidence: 99%
“…However, in contrast to oxazole derivatives, imidazole N ‐oxides are much more stable compounds, especially with alkyl substituents in N(1) or carbamoyl group at C(4) which prove a strong intramolecular hydrogen bond with an oxygen atom of the N ‐oxide group. Therefore, the chemistry of 2‐unsubstituted imidazole N ‐oxides had been intensively developed, especially in the last 10–15 years [5a–c] …”
Section: Introductionmentioning
confidence: 99%